Implementation of Student Performance Management Guidance to Improve Quality Study at Colleges - Dolan, Ellen; Bein, Adrian Sean (Pandawan Sejahtera Indonesia, 2020)
Student attendance activities can take place well and smoothly With a very active student to attend each attendance Student guidance in completing the research. With it, it takes Attentive attention to the student's attendance. Known systems that have an important role for student guidance are the Attendance assessment system and the higher education service system that is absolutely necessary for lecturers Supervisor for monitoring research at higher education. One of the media information is a very important Viewboard in the The Pen System (attendance Assessment) on the Viewboard Pen used for Assessment of attendance of students to get complete data and accuracy. However, existing Viewboard Pens do not currently have a Viewboard Performance that can be a benchmark in comparing Student attendance. There are 3 (three) issues that cause Alternative problems include the absence of information to display Reanytime Student attendance for a certain period of time. Furthermore, the absence of Performance graphs that can measure the performance of student attendance, And the absence of search filters for a certain period of time. Therefore, Designed a Viewboard using the Bootstrap template and also Using the SWOT method. Using 4 (four) methods System analysis using user requirement, design method Using Prototype, HIPO, Flowchart and UML (Unified Modelling Language). The Viewboard Pen is designed using Yii Framework and hopefully helpful in solving problems Attendance at the previous system and motivating students Guidance to be more active.